MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH BERKOMPETENSI KEWIRAUSAHAAN DI DI YAYASAN AL FALAH GEDONGAN BAKI SUKOHARJO TAHUN 2021 - Indah Nurhidayati (Institut Islam Mamba'ul 'Ulum Surakarta, 2021)
The purpose of this research is to find out; (1) leadership management of school principals with entrepreneurial competence, (2) barriers to conducting leadership management of entrepreneurial competent principals, (3) solutions in overcoming obstacles. This study uses descriptive qualitative research methods. The research was conducted at the Al Falah Gedongan Baki Sukoharjo Foundation, May-June 2021. Research subjects: Principals and Al Falah Foundation. Informants : (1) employees (2) committee (3) guardians (4) students. Data collection techniques using observation, interviews, and documentation. The technique of checking the validity of the data uses triangulation with the source. Data analysis techniques using interactive methods include data collection, data reduction, data presentation and drawing conclusions. The results of this study; (1) The leadership management of school principals with entrepreneurial competence at the Al Falah Foundation; The ability to create effective, efficient, and unique schools is carried out through innovative management. One-roof schools that are managed starting from KB, Kindergarten, MI/SD, MTs/SMP, MA/SMA and Pondok. Excellent school activity programs and expertise such as Tahsin and Tahfidz, memorizing prayers and dhikr, memorizing selected verses and hadith, muhadaroh (speech), Arabic, Computer (IT), English and character culture. (2); There are still teachers who are not yet optimal in doing entrepreneurship, and it is still impressed that there is a frequency of delays for teachers in following technological developments, being less active in developing their potential. (3) Solutions; Cooperating with various parties including BMT financial institutions, providing motivation to educators to become entrepreneurs; conduct regular coaching with regard to entrepreneurial insight; conduct a screening on the experience of developing work.